Subsidized or Not, the Impact of Firm Internationalization on Green Innovation—Based on a Dynamic Panel Threshold Model - Chen, Pengyu (Frontiers in Environmental Science, 2022)
To alleviate the increasingly serious environmental problems, the environmental governance of relevant firms has received widespread attention. In this paper, based on panel data of Chinese listed firms from 2010-2019, we use the dynamic panel model to verify the non-linear relationship between internationalization and green innovation performance. The dynamic panel threshold model is also constructed to estimate the threshold effect of subsidies between internationalization and green innovation performance. The results show that there is a “U” relationship between internationalization and green innovation. Subsidies can help firms cross the inflection point earlier, and internationalization positively affects green innovation output only when the subsidy exceeds the threshold (16.994). Considering the heterogeneity issue, our study finds that the subsidy threshold for internationalization is bigger for state-owned, non-coastal enterprises, and enterprises with environmental information disclosure compared to other enterprises. In addition, when across the subsidy threshold, state-owned, non-coastal enterprises, and enterprises without environmental information disclosure are better able to stimulate green innovation output. This provides evidence and policy directions for other emerging developing countries.